Engagement and academic satisfaction in university administration students in Arequipa, 2024 - Huanca Riveros, Kevin; Mariluz Barrientos, Pedro; Villegas Alvarez, Jeanmarco (LACCEI, 2025)
The research was established to determine the relationship between academic engagement and academic satisfaction of university students studying a career in administration. The methodology used was applied, quantitative approach, with a non-experimental, cross-sectional and correlational design. This study was carried out in the city of Arequipa, whose sample was made up of students from 6 private universities and 1 public university with a total number of 423 university students in the city of Arequipa. The following instruments were applied: Utrecht Work Engagement Scale - 17 (UWES-17) and Academic Satisfaction Scale (ESA), which have the respective validity and reliability. According to the statistical analysis, a significant relationship was found between both variables; however, the dimensions of absorption and dedication have a higher positive index, while the dimension of vigor has a lower positive incidence with academic satisfaction. The analysis of the results suggests that universities should implement updated psychological evaluation methods and apply them periodically to optimize their performance, fostering commitment and effectiveness, to maintain student productivity, universities should reformulate academic methods that preserve their potential and energy in the face of daily changes, thus increasing the perceived reward. In summary, knowing these results and the above mentioned, it can be concluded that, in order to achieve optimal and beneficial behavior and performance, it is essential to work on the psychological well-being of students, actively participating in the learning and adaptation process.